OBJECTIVE AND SUBJECTIVE MEASURES OF BUSINESS PERFORMANCE - Kotane, Inta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
To characterise the results of company’s business activities, the term ‘performance’ is used in the foreign scientific and educational literature. Objective and subjective measures are used in the international practice to measure the business performance. In Latvia, evaluation and systematization of these measures has not been carried out, which justifies the necessity of theoretical exploration of the objective and subjective performance measures. The study is based on the analysis of specialised literature and foreign scientific publications on the performance measurement issues. The following general research methods are used in the study: monographic or descriptive research method and comparison method. Aim of the research: to carry out a theoretical study on the objective and subjective measures of business performance. In the result of the research, evaluation and systematization of the objective and subjective performance measures is carried out. Subjective assessment of the company's performance includes the comparison of the company's financial and/or non-financial performance indicators with the competitors'/the main competitor's financial and/or non-financial performance indicators, or the industry’ s average values. Objective assessment of the company's performance determines the necessity of using the information contained in the company's financial statements.